Albizia Adianthifolia: Botany, Medicinal Uses, Phytochemistry, and Pharmacological Properties - Alfred Maroyi (The Scientific World Journal, 2018)
The bark, leaves, and roots of Albizia adianthifolia are highly sought after in tropical Africa as herbal medicines. Therefore, the aim of this study was to review the botany, medicinal uses, phytochemistry, and pharmacological properties of A. adianthifolia so as to provide baseline data required for evaluating the therapeutic potential of the species. Information on the botanical profile, medicinal uses, phytochemistry, and pharmacological properties of A. adianthifolia was undertaken using databases such as ScienceDirect, SciFinder, Pubmed, Google Scholar, Medline, SCOPUS, EThOS, ProQuest, OATD, and Open-thesis. Preelectronic literature search of conference papers, scientific articles, books, book chapters, dissertations, and theses was carried out at the University library. Literature search revealed that A. adianthifolia is used as purgative and herbal medicine for diabetes, eye problems, gastrointestinal problems, haemorrhoids, headache, neurodegenerative disorders, reproductive problems in women, respiratory problems, wounds and pain, skin diseases, sexually transmitted infections, and ethnoveterinary medicine. Phytochemical compounds identified from the species include apocarotenoids, chalcone, dipeptide, elliptosides, essential oils, fatty acids, flavonoids, histamine, imidazolyl carboxylic acid, prosapogenins, steroids, triterpene saponins, and triterpenoids. Pharmacological studies revealed that A. adianthifolia extracts and compounds have acetylcholinesterase enzyme inhibitory, anthelmintic, antiamoebic, antibacterial, antimycobacterial, anti-sexually transmitted infections, antifungal, anti-inflammatory, antioxidant, anxiolytic, and antidepressant, cognitive-enhancing, haemolytic, hypoglycemic and antihyperglycemic, immunomodulatory, and cytotoxicity activities. Detailed studies on the pharmacokinetics, in vivo, and clinical research involving compounds isolated from A. adianthifolia and extracts of the species are required.